Thyroxine changes in COVID-19 pandemic: A systematic review and meta-analysis - Li, Ziqi; Hou, Pengwei; Mu, Shuwen; Wang, Renzhi; Miao, Hui; Feng, Ming; Wang, He; Zhang, Wentai; Chen, Yihao; Feng, Tianshun; Wang, Shousen; Fang, Yi (Frontiers in Endocrinology, 2023)
Objective COVID-19 infection may affect thyroid function. However, changes in thyroid function in COVID-19 patients have not been well described. This systematic review and meta-analysis assess thyroxine levels in COVID-19 patients, compared with non-COVID-19 pneumonia and healthy cohorts during the COVID-19 epidemic. Methods A search was performed in English and Chinese databases from inception to August 1, 2022. The primary analysis assessed thyroid function in COVID-19 patients, comparing non-COVID-19 pneumonia and healthy cohorts. Secondary outcomes included different severity and prognoses of COVID-19 patients. Results A total of 5873 patients were enrolled in the study. The pooled estimates of TSH and FT3 were significantly lower in patients with COVID-19 and non-COVID-19 pneumonia than in the healthy cohort (P < 0.001), whereas FT4 were significantly higher (P < 0.001). Patients with the non-severe COVID-19 showed significant higher in TSH levels than the severe (I2 = 89.9%, P = 0.002) and FT3 (I2 = 91.9%, P < 0.001). Standard mean differences (SMD) of TSH, FT3, and FT4 levels of survivors and non-survivors were 0.29 (P= 0.006), 1.11 (P < 0.001), and 0.22 (P < 0.001). For ICU patients, the survivors had significantly higher FT4 (SMD=0.47, P=0.003) and FT3 (SMD=0.51, P=0.001) than non-survivors. Conclusions Compared with the healthy cohort, COVID-19 patients showed decreased TSH and FT3 and increased FT4, similar to non-COVID-19 pneumonia. Thyroid function changes were related to the severity of COVID-19. Thyroxine levels have clinical significance for prognosis evaluation, especially FT3.